Senescent cell depletion alleviates obesity-related metabolic and cardiac disorders - Tábatha de Oliveira Silva; Guilherme Lunardon; Caroline A. Lino; Amanda de Almeida Silva; Shiju Zhang; Maria Cláudia Costa Irigoyen; Yao Wei Lu; John D. Mably; Maria Luiza M. Barreto-Chaves; Da-Zhi Wang; Gabriela P. Diniz (Molecular Metabolism)
Obesity is a major contributor to metabolic and cardiovascular disease. Although senescent cells have been shown to accumulate in adipose tissue, the role of senescence in obesity-induced metabolic disorders and in cardiac dysfunction is not yet clear; therefore, the therapeutic potential of managing senescence in obesity-related metabolic and cardiac disorders remains to be fully defined. Objective: We investigated the beneficial effects of a senolytic cocktail (dasatinib and quercetin) on senescence and its influence on obesity-related parameters. Methods and Results: We found that the increase in body weight and adiposity, glucose intolerance, insulin resistance, dyslipidemia, hyperleptinemia, and hepatic disorders which were induced by an obesogenic diet were alleviated by senolytic cocktail treatment in mice. Treatment with senolytic compounds eliminated senescent cells, counteracting the activation of the senescence program and DNA damage in white adipose tissue (WAT) observed with an obesogenic diet. Moreover, the senolytic cocktail prevented the brown adipose tissue (BAT) whitening and increased the expression of the thermogenic gene profile in BAT and pWAT. In the hearts of obese mice, senolytic combination abolished myocardial maladaptation, reducing the senescence-associated secretory phenotype (SASP) and DNA damage, repressing cardiac hypertrophy, and improving diastolic dysfunction. Additionally, we showed that treatment with the senolytic cocktail corrected gene expression programs associated with fatty acid metabolism, oxidative phosphorylation, the P53 pathway, and DNA repair, which were all downregulated in obese mice. Conclusions: Collectively, these data suggest that a senolytic cocktail can prevent the activation of the senescence program in the heart and WAT and activate the thermogenic program in BAT. Our results suggest that targeting senescent cells may be a novel therapeutic strategy for alleviating obesity-related metabolic and cardiac disorders.